Perineuronal nets decrease membrane capacitance of peritumoral fast spiking interneurons in a model of epilepsy. Issue 1 (December 2018) - Tewari, Bhanu; Chaunsali, Lata; Campbell, Susan; Patel, Dipan; Goode, Adam; Sontheimer, Harald
Abstract Brain tumor patients commonly present with epileptic seizures. We show that tumor-associated seizures are the consequence of impaired GABAergic inhibition due to an overall loss of peritumoral fast spiking interneurons (FSNs) concomitant with a significantly reduced firing rate of those that remain. The reduced firing is due to the degradation of perineuronal nets (PNNs) that surround FSNs. We show that PNNs decrease specific membrane capacitance of FSNs permitting them to fire action potentials at supra-physiological frequencies. Tumor-released proteolytic enzymes degrade PNNs, resulting in increased membrane capacitance, reduced firing, and hence decreased GABA release. These studies uncovered a hitherto unknown role of PNNs as an electrostatic insulator that reduces specific membrane capacitance, functionally akin to myelin sheaths around axons, thereby permitting FSNs to exceed physiological firing rates. Disruption of PNNs may similarly account for excitation-inhibition imbalances in other forms of epilepsy and PNN protection through proteolytic inhibition may provide therapeutic benefits. Brain tumours are associated with epilepsy. Here the authors show, using a mouse model, that the degradation of perineuronal nets around fast spiking interneurons near the tumour contribute to seizures by increasing their membrane capacitance and firing.